The rise of street veterinary medicine and the benefits it provides for unhoused individuals and their companion animals - Hall, Joslin, author (Colorado State University. Libraries, 2024)
This research explores the rise of street veterinary medicine and its benefits for unhoused individuals and their companion animals. Through volunteering with The Street Dog Coalition, a nonprofit organization providing veterinary care to pets of the unhoused and at risk of homelessness. This thesis examines the physical and mental health impacts of pet ownership within this community. Drawing on personal volunteer experiences, interviews with organization staff, and review of relevant literature, this paper highlights the essential role pets play in bolstering the emotional support, purpose, and resilience for their owners quality of life. It also discusses the challenges and sacrifices faced by unhoused pet owners, including barriers to housing and healthcare access, and focuses on the need for integrated, pet-inclusive support systems. This study promotes a "one health" approach, which provides necessary medical care for both humans and animals, and emphasizes the importance of maintaining the human-animal bond while addressing broader social issues.
Colorado State University Honors Program.
Keywords: veterinary medicine; community service; unhoused community; pet ownership; mental health